Daur Ulang Film: Intertekstualitas Miracle in Cell No.7 (2022) - Noor, Firdaus (Urban: Jurnal Seni Urban, 2022)
How are textual relationships smuggled into recycled film? when and where does this process stop? If it ends, what is the recycled film like after being fucked with meaning? It is these questions that the writer poses in analyzing the inter-text relationships contained in the film Miracle in Cell No. 7 original version (South Korea) and Indonesian version remake. The Indonesian version of Hanung Bramantyo’s work is the result of recycling activities while broadening and deepening the elements of the original source, while still guarding his personal aesthetic corridor. By using a qualitative paradigm, the approach is carried out by using textual studies on recycled films, especially in the structure that is produced compared to the narrative findings of the original film model. This paper attempts to provide a broad and systematic approach to the phenomenon of cinematic remake based on the theory of intertextuality. The research results reveal a fundamental proposition about the conception of film recycling. The results of the study also show that every time a recycled film is created, there will actually be a change in the original text such as a quote that is grafted into a new context through a cultural background that forms narrative and cinematic content, and thus it is inevitable that the work will be reflected and then disseminated.Bagaimana hubungan antarteks diselundupkan ke dalam film daur ulang? kapan dan di mana proses ini berhenti? Jika berakhir, seperti apakah film daur ulang setelah disetubuhi makna? Pertanyaan-pertanyaan inilah yang penulis ajukan dalam menganalisis hubungan antarteks yang termuat dalam film Miracle in Cell No. 7 versi asli (Korea Selatan) dan remake versi Indonesia. Karya Hanung Bramantyo versi Indonesia tersebut merupakan hasil kegiatan mendaur ulang sembari memperluas dan memperdalam unsur-unsur sumber aslinya, sekaligus tetap mengawal koridor personal estetiknya. Dengan menggunakan paradigma kualitatif, pendekatan dilakukan dengan menggunakan kajian tekstual pada film daur ulang, khususnya di bagian struktur yang diproduksi dibandingkan dengan penemuan naratif model film aslinya. Tulisan ini berusaha memberikan pendekatan yang luas dan sistematis terhadap fenomena remake sinematik berdasarkan teori intertekstualitas. Hasil penelitian menyingkap satu proposisi mendasar tentang konsepsi daur ulang film. Hasil penelitian juga menunjukkan bahwa setiap terciptanya daur ulang film sejatinya akan terjadi pengubahan teks asli seperti sebuah kutipan yang dicangkokkan ke dalam konteks baru melalui latar budaya yang membentuk konten naratif maupun sinematik, dan dengan demikian tidak terelakkan karya tersebut akan direfleksikan lalu disebarluaskan.